PIEZO1 mechanoreceptor activation reduces adipogenesis in perivascular adipose tissue preadipocytes - Rendon, C. Javier; Flood, Emma; Thompson, Janice M.; Chirivi, Miguel; Watts, Stephanie W.; Contreras, G. Andres (Frontiers in Endocrinology, 2022)
During hypertension, vascular remodeling allows the blood vessel to withstand mechanical forces induced by high blood pressure (BP). This process is well characterized in the media and intima layers of the vessel but not in the perivascular adipose tissue (PVAT). In PVAT, there is evidence for fibrosis development during hypertension; however, PVAT remodeling is poorly understood. In non-PVAT depots, mechanical forces can affect adipogenesis and lipogenic stages in preadipocytes. In tissues exposed to high magnitudes of pressure like bone, the activation of the mechanosensor PIEZO1 induces the differentiation of progenitor cells towards osteogenic lineages. PVAT’s anatomical location continuously exposes it to forces generated by blood flow that could affect adipogenesis in normotensive and hypertensive states. In this study, we hypothesize that activation of PIEZO1 reduces adipogenesis in PVAT preadipocytes. The hypothesis was tested using pharmacological and mechanical activation of PIEZO1. Thoracic aorta PVAT (APVAT) was collected from 10-wk old male SD rats (n=15) to harvest preadipocytes that were differentiated to adipocytes in the presence of the PIEZO1 agonist Yoda1 (10 µM). Mechanical stretch was applied with the FlexCell System at 12% elongation, half-sine at 1 Hz simultaneously during the 4 d of adipogenesis (MS+, mechanical force applied; MS-, no mechanical force used). Yoda1 reduced adipogenesis by 33% compared with CON and, as expected, increased cytoplasmic Ca2+ flux. MS+ reduced adipogenesis efficiency compared with MS-. When Piezo1 expression was blocked with siRNA [siPiezo1; NC=non-coding siRNA], the anti-adipogenic effect of Yoda1 was reversed in siPiezo1 cells but not in NC; in contrast, siPiezo1 did not alter the inhibitory effect of MS+ on adipogenesis. These data demonstrate that PIEZO1 activation in PVAT reduces adipogenesis and lipogenesis and provides initial evidence for an adaptive response to excessive mechanical forces in PVAT during hypertension.